HISTORY OF RUSSIA-UKRAINE RELATIONS & ITS IMPACT ON THE U.S. & INDIA - Samindra Mohan Biswas (Khazanah Multidisiplin, 2023)
Ukraine has been dogged by corruption scandals, economic mismanagement, and Russian interference since it's independence in 1991, when amidst the dissolution of Soviet Union, Ukraine voted for independence with 92 per cent Ukrainians voting for independence and elected Leonid Kravchuk as President. In fact, Ukraine had the second largest population and economy of the fifteen Soviet Republics. In January 14, 1994, the Russian, Ukrainian and U.S. Presidents signed a statement reaffirming Ukraine's commitment to transfer all strategic nuclear warheads to Russia and dismantle strategic launchers in it's territory. In February 8, 1994, the North Atlantic Treaty Organization welcomed Ukraine into it's partnership for peace, a collaborative arrangement opened to all non-NATO European countries and post-Soviet states and this was the turning point in the Ukrainian relationship with Russia as Russia felt hurt and loss of prestige to the Western world. Moreover, in order to secure and protect her interests and threatened by western alliance, Russia invaded Ukraine in February, 2014 and seized and annexed Crimea on March 21, 2014, though already in August, 2008, Russia had invaded Georgia and made Abkhazia and South Ossetia independent. The renaming of Ukraine as NATO Enhanced Opportunities' Partner in June, 2020 added fuel to the fire.The finishing of Natural Gas Pipeline Nord 2, under the Baltic Sea to Germany in September, 2021 by Russian firm Gazprom resulted in strong protests from Kyiv and the U.S. fearing a cut off of income because of this project. (1) But Russia feeling insecure finally launched an invasion of Ukraine on February 24, 2022 thus endangering international peace which had an impact on third world countries like India. This article has tried to focus on the fact that India being a non-aligned country and one of the founder members of NAM and the Third World dating back to the cold war era and having good relations with both the U.S. and Russia especially the latter stands up to the situation. Because Russia has always stood behind India during crisis period along with the fact that India is a buyer of oil from Russia at a cheap price. Again, India's recent closeness with the U.S. has put India's position in a dilemma in the perspective of International relations more so in the face of threat from China which is looming large as time is passing by. It has been seen in the past getting help from the West especially the U.S. is a bit problematic. So, this writing has tried to stress that India will have to very carefully tread it's path diplomatically and politically keeping her interests and also the long-standing friendship with Moscow since the time of erstwhile Soviet Union. The question will India be successful in following this?